Mata Kuliah Pendidikan Kewarganegaraan terhadap Perilaku Kehidupan Mahasiswa - Nofriansyah, Deny; Irwansyah, Yadri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of the Civics Education course on the behavior of students at PGRI Silampari University, Lubuklinggau. The method used was a quantitative survey approach with 87 respondents who had taken the Civics Education course. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis used a simple linear regression test. The results showed a significant influence between Civics Education and student behavior, with a significance value of 0.000 (<0.05) and a coefficient of determination of 0.716. In conclusion, the Civics Education course contributed 71.6% to shaping students' behavior, thus playing a strategic role in shaping student character in higher education. Keywords: Character Education, Civics Education, Higher Education Students, Student Behavior